2012
DOI: 10.1080/09205063.2012.735099
|View full text |Cite
|
Sign up to set email alerts
|

Balancing mechanical strength with bioactivity in chitosan–calcium phosphate 3D microsphere scaffolds for bone tissue engineering: air- vs. freeze-drying processes

Abstract: The objective of this study was to evaluate the potential benefit of 3D composite scaffolds composed of chitosan and calcium phosphate for bone tissue engineering. Additionally, incorporation of mechanically weak lyophilized microspheres within those air-dried (AD) was considered for enhanced bioactivity. AD microsphere, alone, and air- and freeze-dried microsphere (FDAD) 3D scaffolds were evaluated in vitro using a 28-day osteogenic culture model with the Saos-2 cell line. Mechanical testing, quantitative mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Air drying of this scaffold enhances its bioactivity. Given its optimum strength, degradation resistance, and cell-supportive characteristics, chitosan can be used for bone tissue engineering [86]. …”
Section: Structure and Properties Of Grafts And Bone Substitutesmentioning
confidence: 99%
“…Air drying of this scaffold enhances its bioactivity. Given its optimum strength, degradation resistance, and cell-supportive characteristics, chitosan can be used for bone tissue engineering [86]. …”
Section: Structure and Properties Of Grafts And Bone Substitutesmentioning
confidence: 99%
“…Just like randomly combining HAp and collagen is no guarantee that a composite structure as stable and sturdy as bone will be produced, so does it frequently occur that two composites formed from identical components, but by slightly different means, yield drastically different end results. Such was the case with chitosan-HAp scaffolds whereby the air-dried ones demonstrated a threefold increase in compressive strength over the freeze-dried ones 167 , suggesting that even at the final processing stages changes can occur that dramatically affect the interaction of the components at the nano and molecular scales. After all, if sheer solvent desorption and resorption was enough to cause reversible structural transformations in 3-nm-sized zinc sulfide particles 168 , the structure of softer nanoparticles must be even more amenable to such post-processing effects.…”
Section: Other Composite Materialsmentioning
confidence: 98%
“…Also, another study reported that an inorganic bovine bone has no osteoinductivity and its granular form makes it difficult to be fixed on surgical sites. Moreover, the bovine xenograft is non-absorbable in vivo [58].…”
Section: (Iii) Xenograftsmentioning
confidence: 99%